Cyber security and Maqasid Al-shariah: a case of Facebook application - Ahmad H.Osman, Rahmah; Zakariyah, Luqman; Zakariyah, Habeebullah; Ahmad Dahlan, Abdul Rahman (Global Academic Excellence (GAC) Sdn. Bhd, 2020)
Man has experienced a tremendous advancement in his way of communication due to the technological breakthrough which reached the apex in the recent years. Specifically, the importance of social media has become significant as it spans several spectrums of human life. Thus, cybersecurity is becoming an issue of paramount importance since the amount of information and technology available on cyberspace is skyrocketing. This study was an attempt to present the Maqasidic analysis of the benefits derived from the use of Facebook use as a social media platform, as well as the security threats facing cyber users while using the application. Using the Maqasid al-Shariah (The higher objectives of Islam) as the basis, the researcher found that Facebook users derive certain benefits from their Facebook use and this assists them to achieve Maqasid al-Shariah’s higher objectives. Nevertheless, human beings are faced with certain security threats which hamper their achievements of these Maqasid higher objectives. The researchers then proposed some guidelines and principles by which cyber security can be best achieved through the Maqasid al-Shariah.